A man of many interests: Plutarch on religion, myth, and magic : essays in honor of Aurelio Pérez Jiménez - Pérez Jiménez, Aurelio; Leão, Delfim Ferreira; Roig Lanzillotta, Lautaro (Brill's Plutarch studies, 2020)
"The title of this volume A Man of Many Interests: Plutarch on Religion, Myth, and Magic. Essays in honour of Aurelio Pérez Jiménez is first and foremost a coalescing homage to Plutarch and to Aurelio, and to the way they have been inspiring (as master and indirect disciple) a multitude of readers in their path to knowledge, here metonymically represented by the scholars who offer their tribute to them. The analysis developed throughout the several contributions favors a philological approach of wide spectrum, i.e., stemming from literary and linguistic aspects, it projects them into their cultural, religious, philosophical, and historical framework. The works were organized into two broad sections, respectively devoted to the Lives and to the Moralia. Contributors are: Frances Titchener, Carlos Alcalde Martín, José Luis Calvo, Delfim Leão, Judith Mossman, Anastasios G. Nikolaidis, Christopher Pelling, Philip Stadter, Paola Volpe, Francesco Becchi, Israel Muñoz Gallarte, Lautaro Roig Lanzillotta, Geert Roskam, Vicente M. Ramón Palerm, Frederick Brenk, John Dillon, Franco Ferrari, Aristoula Georgiadou, Luc van der Stockt, Luisa Lesage Gárriga"--